Product design optimisation with microstructure-property modelling and associated uncertainties. (18th September 2009) - Solanki, K.N.; Acar, Erdem; Rais-Rohani, M.; Horstemeyer, M.F.; , W.G. Steele
In this paper, we present a methodology for simulation-based product design optimisation using an internal state variable (ISV) constitutive modelling approach that captures the microstructure-property relations in the material. By modelling the stochastic uncertainties in the material model and the loading conditions, the design optimisation problem is formulated and solved using the reliability-based design optimisation (RBDO) methodology. The application problem considers the design optimisation of an A356-T6 cast aluminium component under maximum stress and damage constraints. Alternative metamodelling techniques are used to develop appropriate surrogate models in lieu of direct coupling of non-linear static finite element analysis and numerical design optimisation. Probabilistic design constraints are modelled using the safety index approach with the solution of the nested optimisation problem facilitated with the help of analytical surrogate models. Comparison of the optimisation results reveals the importance of using an ISV-based constitutive model that is sensitive to the growth of damage in material. Moreover, the solution of the RBDO problem captures the effects of uncertainty on finding the minimum weight design for the cast component.